Generating Orally-Active Galanin Analogs with Analgesic Activities - Robertson, Charles R. (ChemMedChem, 2012)
The endogenous neuropeptide galanin has anticonvulsant and analgesic properties mediated by galanin receptors expressed in the central and peripheral nervous systems. Our previous work showed that combination of truncation of the galanin peptide along with N-and C-terminal modifications afforded analogs that suppressed seizures or pain following intraperitoneal administration. To generate orally-active galanin analogs, the previously reported lead compound Gal-B2 (NAX 5055) was redesigned by (1) central truncation, (2) introduction of D-amino acids, (3) and addition of backbone spacers. Analog D-Gal(7-Ahp)-B2, containing 7-amino heptanoic acid as a backbone spacer and oligo-D-lysine motif at the C-terminus, exhibited anticonvulsant and analgesic activity post intraperitoneal administration. Oral administration of D-Gal(7-Ahp)-B2 demonstrated analgesic activity with reduction in both acute and inflammatory pain in the mouse formalin model of pain at doses as low as 8 mg/kg.